Fragile Lines: Climate-Security Nexus on Power Transmission Infrastructure (Journal of Asian Development Studies, 2024)
Pakistan ranks top ten countries worst hit by climatic changes, as climate-related events become habitual, these disruptions produce terrain facilitative to theft and vandalism, thereby complicating / intensifying existing challenges and trapping the system in vicious circle of clime-security nexus. This paper explores complicated relationship between climate and physical security within power transmission sector, a crucial lynchpin in energy system. By emphasizing on compounded vulnerabilities arising from climate-induced disruptions and accelerating security threats, the study aims unveiling its nexus in Pakistan Electric Transmission Networks. Employing Barry Buzan's “Five Sectors of Security” frame and triangulation approach, the study carried out detailed investigation of records, collected data physically and performed interviews of key stake holders to get practical insights into climate-security nexus. Findings reveal significant climate-security nexus damaging the power systems, wherein environmental stressors amplify physical security challenges, the complex statistical tests conducted on data set showed strong significant results also positive correlation between the two variables i.e. climatic impacts and physical security incidents on power transmission system, the study also revealed as to how positive feedback (virtuous cycle) and negative feedback (vicious cycle) operate in this nexus. Paper emphasizes and recommends critical need for visionary responses to these interlinked challenges and responses which are required for enhanced reliability / resilience of energy systems, thereby promoting socio-economic stability / sustainability by enhancing National Security posture and safeguarding effective economic balance of power in South Asia.